Implementation of Construction Services Procurement at the Vocational High School Center of Excellence (SMK PK) in DKI Jakarta - Sanktiaji, Bayu Eka (Indonesian Journal Publisher, 2024)
In the era of the development of the industrial world, construction services in the world of education, especially in Central High Schools of Excellence, are very intensively carried out in order to achieve the objectives of the SMK PK program, namely to improve the quality of human resources through government assistance which focuses on student practice rooms and industrial standards. The fulfillment of these facilities and infrastructure is carried out by procuring in accordance with the reference, namely Permendikbud No.18 of 2022. The purpose of this study is to increase knowledge and information related to good procurement procedures and ethics carried out by SMK PK. The method used is literature review. The results show that the facilities and infrastructure at SMK PK are very good because they are followed by the implementation of procurement according to procedures and ethics. Starting from planning, determining providers, making agreements, and carrying out procurement in accordance with Permendikbud No.18 of 2022.